Exploring Investment Preparedness in Generation Z Through the Lens of Self-Determination Theory - Muh. Yahya; Rusni Andrianirani; Risal; Nurafini Anggraini (Fundamental and Applied Management Journal, 2024)
In the wake of the financial challenges brought on by the Coronavirus pandemic, many Indonesians have taken steps to allocate their funds or secure future financial gains through various means, including savings and prudent financial planning. This study aims to explore the investment preparedness of students at Universitas Negeri Makassar through the lens of Self-Determination Theory. This theory emphasizes the role of intrinsic motivation, competence, and relatedness in shaping individual behavior. The research employs a quantitative approach, collecting data through surveys designed according to the principles of Self-Determination Theory. These surveys assess the level of investment preparedness among students and the factors influencing it. The findings are expected to provide valuable insights into the factors that impact students' readiness to invest and the implications for financial education programs on campus. By understanding these factors, educators can better support students in developing the skills and motivation needed to make informed investment decisions, ultimately contributing to their financial well-being and future success.